Analysis of Factors Influencing the Level of Income of UMKM Business Owners in the Food Sector in Medan Sunggal District - Marisya Gultom; Rusiadi (PT FORMOSA CENDEKIA GLOBAL, 2024)
The income generated from an MSME business is greatly influenced by production factors, so this study also wants to see what factors influence the income of MSME actors.CFA model (Confirmatory Factor Analysis)where this model is used to summarize several variablesand continued using multiple linear regression. Analyzing the existing factors including capital, raw materials, technology, price, business location and labor with data obtained from 90 UMKM business actors in Medan Sunggal District. The results of the analysis of factors that determine raw materials, prices and labor as the largest contribution to multiple linear regression show that the influence of raw materials and prices is significant and labor has no significant influence on income